Teacher sensitivity as a bridge to emotion regulation for students with special educational needs in their emotional and social development in physical education - Brunssen, Leefke; Kastrup, Valerie (Frontiers in Sports and Active Living, 2025)
IntroductionStudents with special educational needs in their emotional and social development (SEN-ESD) often experience strained teacher-student relationships (TSR). Physical Education (PE) presents a dual-natured context: while offering explicit curricular socioemotional learning opportunities, its embodied interactions and open setting may feel overwhelming for these students. Cross-disciplinary research on SEN-ESD suggests scarcity of qualitative work centering student and secondary teacher voices concerning TSR. Guided by attachment theory, this qualitative study investigated: (1) how students with SEN-ESD and PE teachers perceive the affective quality of their TSR in inclusive PE settings, and (2) what concepts are related to the perceived affective quality of TSR.Materials and methodsUsing Grounded Theory, we conducted and analyzed semi-structured interviews iteratively with 22 students (ages 10–16) with formal SEN-ESD diagnoses and 18 PE teachers at German regular secondary schools until theoretical saturation was achieved.ResultsAnalysis revealed three interrelated dimensions: (1) the category perceived TSR quality (conflict ↔ closeness); (2) the related concept teacher sensitivity (low ↔ high); (3) the related concept students' emotion regulation strategies (dysfunctional ↔ functional).DiscussionAnalysis of the six emergent patterns reveals teacher sensitivity as the pivotal factor shaping teacher-student relational dynamics. Co-constructed agreements foster a secure base for students, supporting functional emotion regulation, whereas rigid rule-enforcement perpetuates cycles of marginalization. Strikingly, some students rationalized aggression as a subjectively functional strategy (e.g., enforcing reciprocity fairness), clashing with systemic norms. Ultimately, the embodied context of PE emerges as a dual-natured relational microcosm: it can offer socioemotional growth when teacher sensitivity is high, but carries escalation risks when subjective-normative discrepancies remain unaddressed.